Influence of tree cover on carcass detection and consumption by facultative vertebrate scavengers - Elke Wenting; Patrick A. Jansen; Luke Pattipeilohy; Peter vanLunteren; Henk Siepel; Frank vanLangevelde (Ecology and Evolution, 2024)
Abstract Scavenging mammals and vultures can exploit and deplete carcasses much faster than other birds and invertebrates. Vultures are strongly influenced by habitat type, e.g. tree cover, since they rely on their eyesight to detect carcasses. It remains unclear whether and how facultative scavengers – both other birds and mammals – are influenced by tree cover and how that affect carcass decomposition time, which in turn affects biodiversity and ecological processes, including the cycle of energy and nutrients. We studied whether the carcass detection and consumption, hence carcass decomposition speed, by facultative avian and mammalian scavengers varies with tree cover in areas without vultures. Fresh mammal carcasses were placed in different landscapes across the Netherlands at locations that widely varied in tree cover. Camera traps were used to record carcass exploitation by facultative avian and mammalian scavengers and to estimate carcass decomposition time. We found that carcass detection and consumption by birds, wild boar, and other mammals varied between locations. Carcass decomposition speed indeed increased with carcass detection and exploitation by mammals, especially by wild boar. However, this variation was not related to tree cover. We conclude that tree cover is not a major determinant of carcass exploitation by facultative scavengers in areas without obligate scavengers and large carnivores.